Does gold act as a hedge and a safe haven for China's stock market? - Ke Chen; Meng Wang (International Journal of Financial Studies, 2017)
This paper examines the dynamic relationships between gold and stock markets in China. Using daily gold and stock indexes data, we estimated the DCC-GARCH model for the five bear markets since 31 October 2002, and simultaneously used different segments of China's stock markets for analysis. Our main objective was to examine the time-varying correlations between gold and stock and to check the effectiveness of gold as a hedge or a safe haven for stocks. Results showed that: (1) the dynamic conditional correlations switched between positive and negative values over the periods under study; (2) due to the increasing investment demand of gold, the hedging effect of gold on China's stock market has strengthened remarkably. Gold acts as a safe haven for only the latest two of the five bear markets analyzed (12 June 2015-26 August 2015 and 22 December 2015-29 February 2016); and (3) for non-bear markets, gold does not offer good risk hedging.
Keywords: G10; G11; G14; G15; 330; gold; bear markets; correlation; safe haven; hedge